30 s Response Time of K+ Ion‐Selective Hydrogels Functionalized with 18‐Crown‐6 Ether Based on QCM Sensor. Issue 5 (6th December 2017) - Zhang, Zhenxiao; Dou, Qian; Gao, Hongkai; Bai, Bing; Zhang, Yongmei; Hu, Debo; Yetisen, Ali K.; Butt, Haider; Yang, Xiaoxia; Li, Congju; Dai, Qing
Abstract: Potassium detection is critical in monitoring imbalances in electrolytes and physiological status. The development of rapid and robust potassium sensors is desirable in clinical chemistry and point‐of‐care applications. In this study, composite supramolecular hydrogels are investigated: polyethylene glycol methacrylate and acrylamide copolymer (P(PEGMA‐ co ‐AM)) are functionalized with 18‐crown‐6 ether by employing surface initiated polymerization. Real‐time potassium ion monitoring is realized by combining these compounds with quartz crystal microbalance. The device demonstrates a rapid response time of ≈30 s and a concentration detection range from 0.5 to 7.0 × 10 −3 m . These hydrogels also exhibit high reusability and K + ion selectivity relative to other cations in biofluids such as Na +, NH4 +, Mg 2+, and Ca 2+ . These results provide a new approach for sensing alkali metal ions using P(PEGMA‐ co ‐AM) hydrogels. Abstract : The polyethylene glycol methacrylate and acrylamide copolymer are functionalized with 18‐crown‐6 ether by employing surface‐initiated polymerization. Real‐time potassium ion monitoring is realized by quartz crystal microbalance. The sensor demonstrates a rapid response time of ≈30 s, a concentration detection range from 0.5 × 10 −3 to 7.0 × 10 −3 m, high reusability and selectivity relative to Na +, NH4 +, Mg 2+, and Ca 2+ .